2018
DOI: 10.1002/acm2.12251
|View full text |Cite
|
Sign up to set email alerts
|

To frame or not to frame? Cone‐beam CT‐based analysis of head immobilization devices specific to linac‐based stereotactic radiosurgery and radiotherapy

Abstract: PurposeNoninvasive frameless systems are increasingly being utilized for head immobilization in stereotactic radiosurgery (SRS). Knowing the head positioning reproducibility of frameless systems and their respective ability to limit intrafractional head motion is important in order to safely perform SRS. The purpose of this study was to evaluate and compare the intrafractional head motion of an invasive frame and a series of frameless systems for single fraction SRS and fractionated/hypofractionated stereotact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
70
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 26 publications
7
70
0
4
Order By: Relevance
“…Babic et al . reported that rotational setup error was the smallest with one of the frame‐based immobilization devices in six head immobilization devices for both frame‐based and flameless SRS and SRT . It should be noted that thermoplastic mask immobilization could bring interfractional shifts of ≤3° in patient position.…”
Section: Discussionmentioning
confidence: 99%
“…Babic et al . reported that rotational setup error was the smallest with one of the frame‐based immobilization devices in six head immobilization devices for both frame‐based and flameless SRS and SRT . It should be noted that thermoplastic mask immobilization could bring interfractional shifts of ≤3° in patient position.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Non-invasive options use one of or a combination of thermoplastic masks, bite blocks, cradles, and optical surface tracking imaging systems to localize and immobilize the brain. 8 In this study, we compared two commercially available devices used in our clinic: Aktina PinPoint™ (non-invasive) 8 and TALON Cranial SRS frame (invasive). 9 Both intra-fraction and inter-fraction setup errors were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Thus no treatment margin beyond the treated target is needed . Non‐invasive options use one of or a combination of thermoplastic masks, bite blocks, cradles, and optical surface tracking imaging systems to localize and immobilize the brain . While the invasive devices can often offer sub‐millimeter positional accuracy, the invasive nature limits their acceptance by patients and deters fractionated treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frameless technique typically involves 1-3 mm planning target volume (PTV) margin. [11][12][13] In particular, rotational errors for targets at distances away from the isocenter would negatively affect the treatment delivery accuracy unless an additional margin is added due to the less effective immobilization and setup with a nonrigid mask system. [14][15][16] Also, accurately positioning the patient for treatment setup for all treatment couch angles becomes the challenge for this approach since multiple targets are treated with one isocenter.…”
mentioning
confidence: 99%